Development and evaluation of an alternative method for processing elastic-lidar return signals - Castrejón García, R; Varela, JR; Castrejón Pita, A; Pita, C (2006)
A method for interpreting elastic-lidar return signals in heavily-polluted atmospheres is presented. It is based on an equation derived directly from the classic lidar equation, which highlights gradients of the atmospheric backscattering properties along the laser optical path. The method is evaluated by comparing its results with those obtained with the differential absorption technique. The results were obtained from locating and ranging measurements in pollutant plumes and contaminated environments around central México. © World Scientific Publishing Company.